PERSEPSI SISWA TENTANG PENGGUNAAN MEDIA DALAM PEMBELAJARAN BAHASA INGGRIS - Rahmadi, Nizar; Ismu Purwaningsih, Dewi; Fauzi Al-Qadri, Yusuf; Yolanda, Alvina (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2024)
The role of media in the learning process is crucial, serving as a key component for effective communication between teachers and students. Without media, this communication process would be hindered, leading to ineffective learning outcomes. To assess the effectiveness of teachers' creativity in utilizing instructional media, it is essential to consider students' perceptions and observations. This study aimed to analyze students' perceptions of the media employed by English teachers at SMP Al-faqihil Muqaddam. Utilizing a qualitative descriptive methodology, the researcher investigated students' responses to the instructional media through observation and interviews. The findings revealed that the media utilized by English teachers included a whiteboard, English book, dictionary, laptop, LCD projector, and speaker. The students' interviews yielded predominantly positive perceptions of the media used in the teaching and learning process. According to the students, the use of media resulted in increased engagement, excitement, and active participation in learning English. They found the materials easier to comprehend, improved their pronunciation and vocabulary, generated new ideas, and felt empowered to express their opinions. Furthermore, they appreciated the practicality of applying what they learned in their daily lives. In conclusion, this research sheds light on the importance of utilizing various media in English language instruction and highlights the positive impact it has on students' learning experiences. By understanding students' perceptions, educators can tailor their instructional approaches to enhance engagement and comprehension, ultimately fostering a more effective learning environment.